1982
DOI: 10.1289/ehp.824647
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic toxicity of chlorine dioxide and related compounds in drinking water in the nonhuman primate.

Abstract: Subchronic toxicities of C1O2, NaCIO2, NaCIO3 and NH2CI were studied in the African Green monkeys (Cercopithecus aethiops). The chemicals were administered in drinking water during 30-60 days subchronic rising dose protocols. The only unexpected and significant toxic effect was elicited by C102; this chemical inhibited thyroid metabolism in the animals at a dose of ca. 9.0 mg/kg/day. A statistically significant decrease of serum thyroxine occurred after the fourth week of exposure to 100 mg/l.concentration. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1
8

Year Published

1984
1984
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 5 publications
(3 reference statements)
1
43
1
8
Order By: Relevance
“…Bercz et al (4) reported that exposure of monkeys to ClO 2 , but not ClO 3 , resulted in decreased serum T 4 levels. In a subsequent study, Harrington, Shertzer, and Bercz (17) noted a decrease in T 4 levels in both rats and monkeys exposed to drinking water containing 0.1 g/L ClO 2 .…”
Section: Histopathologymentioning
confidence: 99%
See 2 more Smart Citations
“…Bercz et al (4) reported that exposure of monkeys to ClO 2 , but not ClO 3 , resulted in decreased serum T 4 levels. In a subsequent study, Harrington, Shertzer, and Bercz (17) noted a decrease in T 4 levels in both rats and monkeys exposed to drinking water containing 0.1 g/L ClO 2 .…”
Section: Histopathologymentioning
confidence: 99%
“…In addition, some data suggest that perchlorate causes a release of accumulated iodide from the gland (3,41). Similarities in thyroid histopathology between perchlorate and chlorate exposure suggest that chlorate may interfere with iodide uptake as well, resulting in stimulation of thyroid follicular cell proliferation mediated by TSH secondary to decreases in T 3 and T 4 . This hypothesis needs to be investigated to determine if the mechanism of chlorate-induced thyroid follicular cell hyperplasia is indeed the same as perchlorate.…”
Section: Histopathologymentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest antithyroidal effects of chlorine or chlorinated products formed when chlorine reacts with organic matter in the upper gastrointestinal tract as it is presumed in pigeons (Revis et al 1986) or the effects of some iodinated molecule forming in trace quantities in the alimentary tract responsible for the thyroid inhibition during chlorine dioxide exposure (Bercz et al 1986). It has also been shown (Bercz et al 1982;Orme et al 1985) that decreased serum thyroxin levels occur in monkeys and neonatal rats during subchronic exposure to chlorine dioxide in drinking water. A significant frequency distribution shift to the smaller follicle categories suggests an increase in the activity of the thyroid gland and/or multiplication of smaller and probably more active follicles.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that chlorine and some other chemicals can form different products when they react with organic matter in the upper gastrointestinal tract. These products exert significant antithyroidal effects (11,12) . Several environmental chemicals have structural similarities to the thyroid hormones thyroxine (T 4 ) and triiodothyronine (T 3 ).…”
Section: Endemic Goitre Iodine Excess Water Chemicals Sudan Schoolchimentioning
confidence: 99%